Ethylene Contributes to maize insect resistance1-Mediated Maize Defense against the Phloem Sap-Sucking Corn Leaf Aphid. Issue 1 (7th August 2015) - Louis, Joe; Basu, Saumik; Varsani, Suresh; Castano-Duque, Lina; Jiang, Victoria; Williams, W. Paul; Felton, Gary W.; Luthe, Dawn S.
Abstract : An endogenous defensive protein in maize that encodes a Cys protease, provides enhanced resistance to phloem sap-consuming pests through the action of an ethylene-signaling pathway. Abstract: Signaling networks among multiple phytohormones fine-tune plant defense responses to insect herbivore attack. Previously, it was reported that the synergistic combination of ethylene (ET ) and jasmonic acid (JA ) was required for accumulation of the maize insect resistance1 ( mir1 ) gene product, a cysteine (Cys) proteinase that is a key defensive protein against chewing insect pests in maize ( Zea mays ). However, this study suggests that mir1 -mediated resistance to corn leaf aphid (CLA ; Rhopalosiphum maidis ), a phloem sap-sucking insect pest, is independent of JA but regulated by the ET -signaling pathway. Feeding by CLA triggers the rapid accumulation of mir1 transcripts in the resistant maize genotype, Mp708. Furthermore, Mp708 provided elevated levels of antibiosis (limits aphid population)- and antixenosis (deters aphid settling)-mediated resistance to CLA compared with B73 and Tx601 maize susceptible inbred lines. Synthetic diet aphid feeding trial bioassays with recombinant Mir1-Cys Protease demonstrates that Mir1-Cys Protease provides direct toxicity to CLA . Furthermore, foliar feeding by CLA rapidly sends defensive signal(s) to the roots that trigger belowground accumulation of the mir1, signifying a potential role of long-distance signaling in maize defense against the phloem-feeding insects. Collectively, our data indicate that ET -regulated mir1 transcript accumulation, uncoupled from JA, contributed to heightened resistance to CLA in maize. In addition, our results underscore the significance of ET acting as a central node in regulating mir1 expression to different feeding guilds of insect herbivores.